"The Job Has Become Advocating for the Job": Threats to Funding Dramatically Influence Program Outcomes. Issue 4 (May 2018) - McCullough, Anna; Ranney, Leah M.; Simons, Daniel J.; Goldstein, Adam O.
As public health funding is increasingly threatened, a better understanding is needed about how periods of funding uncertainty impact program staff, activities, and outcomes. In North Carolina, 2 years of uncertainty and threats of funding cuts for a statewide youth tobacco prevention initiative contributed to reduced grantee morale and confidence about achieving program goals, displaced focus from core program activities, and caused premature loss of personnel, resulting in substantially reduced program activities and outcomes. The range of negative impacts of funding uncertainty and threats highlights the need for programs to create an infrastructure to support ongoing sustainability planning and activities.